Ecological Crisis in Into The Forest by Jean Hegland - Nirmala Khairunnisa Budi; Ali Mustofa (ELite Journal : International Journal of Education, Language, and Literature, 2018)
This study analyzes the relationship between human being and nature in Into the Forest by Jean Hegland. This study uses ecocriticism theory to analyzes the phenomenon of ecological crisis. Ecocriticism is a theory about human being and nature. Nature and human being are related to each other. It is impossible to separate them. When human being exploits nature, it creates a horrible condition for human being and nature. This thesis analyzes the problems, which are: (1) How is nature portrayed, (2) How is the impacts of the devastation of the earth to the human being, and (3) How do the main characters act towards ecological crisis. The result of this study shows that ecological crisis occurs because of the human being. Human wants to fulfill their additional needs, such as war. The main factor of ecological crisis is human desire. It makes famine, disease, barren field, hostility, and death.Keywords: Ecocriticism, Human, Nature, Disaster